Analysis of development grinding wheels on the basis of microcrystalline corundum - Kocman, Karel (Manufacturing Technology Journal, 2010)
Grinding is a finishing operation featuring high precision, correct geometrical form and usually a very good surface quality. One of the factors necessary to achieve needed values is a correct choice and quality of the grinding wheel. The development of new technologies in the field of finishing functional surfaces has been focused on the production of new advanced grinding materials ensuring higher efficiency and reduction of the temperature of contact between the ground surface and the grinding wheel. The desired result is enhanced quality of the ground surfaces. One of the feasible ways of giving a solution to the problem is the application of highly porous grinding materials, sintered corundums. The presented article is focused on the analysis of development grinding wheels containing microcrystalline corundum.
Keywords: Prediction; thermodynamic effects; thermal balance; grinding; Flir 2000